Research on the Actual Dilemma and Countermeasures of the Employment of Graduates of Local Undergraduate Colleges - Huang, Yi (Journal of Theory and Practice of Contemporary Education, 2024)
High-quality employment is school-running "lifeline" and people-cultivation "touchstone" of local undergraduate colleges, the employment situation of college students of local undergraduate colleges is generally stable, employment ideas change rapidly, the structural contradiction of employment is longstanding under the influence of the epidemic, inevitably there are actual dilemmas: high-quality employment faces serious impact, the matching degree between talent development and the market is not high, the career planning of college students is unscientific, etc., efforts should be made to solve the practical problems of graduate employment of local undergraduate colleges, deepen the structural reform of the supply side of college talents, strengthen the joint forces of employment work of local undergraduate college, and improve the employment guidance services of local undergraduate colleges, etc.